Incidence- and In-hospital Mortality-Related Risk Factors of Acute Kidney Injury Requiring Continuous Renal Replacement Therapy in Patients Undergoing Surgery for Acute Type a Aortic Dissection - Chen, Xuelian; Zhou, Jiaojiao; Fang, Miao; Yang, Jia; Wang, Xin; Wang, Siwen; Li, Linji; Zhu, Tao; Ji, Ling; Yang, Lichuan (Frontiers in Cardiovascular Medicine, 2021)
Background: Few studies on risk factors for postoperative CRRT in a homogeneous population of patients with AAAD. This retrospective analysis aimed to investigate risk factors for CRRT and in-hospital mortality in patients undergoing AAAD surgery and to discuss perioperative comorbidities and short-term outcomes. Methods: The study collected electronic medical records and laboratory data from 432 patients undergoing surgery for acute type A aortic dissection between March 2009 and June 2021. All patients were divided into CRRT and non-CRRT groups; those in the CRRT group were divided into survivor and non-survivor groups. Univariate and multivariate analysis were used to identify independent risk factors for CRRT and in-hospital mortality. Results: The proportion of requiring CRRT and in-hospital mortality in CRRT patients, were 14.6% and 46.0%, respectively. Baseline serum creatinine (odds ratio (OR), 1.006), cystatin C (OR, 1.438), lung infection (OR, 2.292,), second thoracotomy (OR, 5.185), diabetes Mellitus (OR, 6.868), AKI stage 2-3 (OR, 22.901) were the independent risk factors for receiving CRRT. In-hospital mortality in the CRRT group (46%) was 4.6 times higher than in the non-CRRT group (10%). In the non-survivor (n=29) and survivor (n=34) groups, New York Heart Association (NYHA) class III-IV (OR, 10.272, P=0.019), lactic acidosis (OR, 10.224, P=0.019) were the independent risk factors for in-hospital mortality in patients receiving CRRT. Conclusion: There was a high rate for requiring CRRT and high in-hospital mortality after AAAD surgery. Clinicians should improve patient prognosis and reduce mortality through better preoperative preparation and management of complications. Further randomised controlled studies are urgently needed to establish the risk factors for CRRT and in-hospital mortality.